Protecting depositors and saving money: Why deposit guarantee schemes in the EU should be able to support transfers of assets and liabilities when a bank fails - Joachim Eule; Wieger Kastelein; Edoardo Sala (European Central Bank (ECB), 2022)
In this paper we show that allowing deposit guarantee schemes (DGSs) the option of supporting asset and liability transfers in the event of a bank's insolvency provides important economic benefits. However, only 11 EU Member States have so far included such "alternative measures" in their DGSs' toolkits. The number of Member States where alternative measures have been actively used is even more limited. Based on our findings, we argue that giving deposit guarantee schemes in the EU the option of using alternative measures would improve the efficiency and effectiveness of the EU banking crisis management framework. It would speed up the handling of smaller banks' failures while reducing upfront outlays and final costs for deposit guarantee schemes. It would improve the protection of deposits, thereby safeguarding depositor confidence and overall financial stability. It would also allow access to finance to be better preserved and enhance the level playing field for banks and depositors in the EU. We also argue that, apart from the availability of the option in law, the least cost test and the creditor hierarchy determine the de facto availability and potential magnitude of alternative measures. Currently, however, both the least cost test and the creditor hierarchy limit the possibility of supporting asset and liability transfers and may therefore need to be reformed in order for economically efficient results to be achieved.
Keywords: G01; G21; G28; 330; Banking union; EU bank crisis management framework; depositguarantee schemes; transfers of assets and liabilities; depositor protection